# To the nearest hundredth, what is the distance between point (-6, -1) and point (4, 3)?

QUESTION POSTED AT 15/01/2020 - 03:11 AM

QUESTION POSTED AT 15/01/2020 - 03:11 AM

The distance between point (-6, -1) and point (4, 3) is **10.77.**

The point (-4, 7) is in the 2nd quadrant. The coordinate of the preimage
of a -90 degrees rotation that resulted to point (-4, 7) will be in the
third quadrant. (i.e. both x and y is negative). Hence, answer is (-7,
-4).

ANSWERED AT 29/01/2020 - 05:41 PM

QUESTION POSTED AT 29/01/2020 - 05:41 PM

That would be C....x^2 - 7x + 6 = (x - 1)(x - 6)

ANSWERED AT 29/01/2020 - 05:40 PM

QUESTION POSTED AT 29/01/2020 - 05:40 PM

Start by combining like terms on both sides

-6+3=-3

Now we have:

To isolate g we need to subtract 12 from both sides -18-12= -30

Now we have

Divide both sides by -3 to isolate g, now we have:

When we divide an inequality by a negative we flip the sign so:

becomes:

Final answer:

ANSWERED AT 29/01/2020 - 05:38 PM

QUESTION POSTED AT 29/01/2020 - 05:38 PM

The domain is all the x values...so he domain is { 6,1,-3}

ANSWERED AT 29/01/2020 - 05:38 PM

QUESTION POSTED AT 29/01/2020 - 05:38 PM

(f + g)(x) = 3x^2 + 2x – 1

g(x) = 2x – 2

f(x) = ? ; 3x^2 + 1

Check by Substituting:

3x^2 + 1 + 2x - 2

Simplify:

3x^2 + 2x - 1

g(x) = 2x – 2

f(x) = ? ; 3x^2 + 1

Check by Substituting:

3x^2 + 1 + 2x - 2

Simplify:

3x^2 + 2x - 1

ANSWERED AT 29/01/2020 - 05:38 PM

QUESTION POSTED AT 29/01/2020 - 05:38 PM

A. At 36 ft/s , it would reach the maximum height in 0.81 seconds

B. Highest height would be 29.25 feet

B. Highest height would be 29.25 feet

ANSWERED AT 29/01/2020 - 05:37 PM

QUESTION POSTED AT 29/01/2020 - 05:37 PM

Area Of Triangle:

4/2 = 2

2x6 = 12

12x2 = 24ft^2

Remaining area:

150 - 24 = 126ft^2

Maximum length:

126/6 = 21

x = 21ft

4/2 = 2

2x6 = 12

12x2 = 24ft^2

Remaining area:

150 - 24 = 126ft^2

Maximum length:

126/6 = 21

x = 21ft

ANSWERED AT 29/01/2020 - 05:37 PM

QUESTION POSTED AT 29/01/2020 - 05:37 PM

**Answer:**

A bisecting line could not be drawn.

**Step-by-step explanation:**

If the compass width was changed, then we could not trace a bisecting line. Different arc measures would not intersect each other, at the center.

So, we would not be able to trace a bisecting line. We would have something like the picture below.

ANSWERED AT 29/01/2020 - 05:37 PM

QUESTION POSTED AT 29/01/2020 - 05:37 PM

10x + 2y = -2

2y = -10x - 2

y = (-10/2)x - 2/2

y = -5x - 1...the slope here is -5...a parallel line will have the same slope.

y = mx + b

slope(m) = -5

(0,12)...x = 0 and y = 12

now we sub...we r looking for b, the y intercept

12 = -5(0) + b

12 = b

so ur parallel line is : y = -5x + 12

2y = -10x - 2

y = (-10/2)x - 2/2

y = -5x - 1...the slope here is -5...a parallel line will have the same slope.

y = mx + b

slope(m) = -5

(0,12)...x = 0 and y = 12

now we sub...we r looking for b, the y intercept

12 = -5(0) + b

12 = b

so ur parallel line is : y = -5x + 12

ANSWERED AT 29/01/2020 - 05:36 PM

QUESTION POSTED AT 29/01/2020 - 05:36 PM

10x + 2y = -2

2y = -10x - 2

y = -(10/2)x - 2/2

y = -5x - 1 y = mx + c, slope m = -5.

If it is parallel, then the slope of the second line ought to be -5 as well.

So you should fill -5 in the bracket.

2y = -10x - 2

y = -(10/2)x - 2/2

y = -5x - 1 y = mx + c, slope m = -5.

If it is parallel, then the slope of the second line ought to be -5 as well.

So you should fill -5 in the bracket.

ANSWERED AT 29/01/2020 - 05:36 PM

QUESTION POSTED AT 29/01/2020 - 05:36 PM

Hello,

As

=π/6+2kπ or -π/6+2kπ

As

=π/6+2kπ or -π/6+2kπ

ANSWERED AT 29/01/2020 - 05:36 PM

QUESTION POSTED AT 29/01/2020 - 05:36 PM

2x + 7y = 4.....multiply by 2

-4x - 3y = 14

------------------

4x + 14y = 8 (result of multiplying by 2)

-4x - 3y = 14

----------------add

11y = 22

y = 2

2x + 7y = 4

2x + 7(2) = 4

2x + 14 = 4

2x = 4 - 14

2x = - 10

x = -5

solution is : (-5,2)

-4x - 3y = 14

------------------

4x + 14y = 8 (result of multiplying by 2)

-4x - 3y = 14

----------------add

11y = 22

y = 2

2x + 7y = 4

2x + 7(2) = 4

2x + 14 = 4

2x = 4 - 14

2x = - 10

x = -5

solution is : (-5,2)

ANSWERED AT 29/01/2020 - 05:36 PM

QUESTION POSTED AT 29/01/2020 - 05:36 PM

Start with given equation .

1. In the right side you have three terms, two of them include p, so you can rewrite right side as

Then the whole equation is

as in option B. This means that option B is true and option A is false (because left sides are the same, but right sides differ).

2. Now multiply the equation by 100:

this equation is exactly as equation in option C. This gives you that option C is true.

3. Now multiply the equation by 10:

this equation differs from the equation in option D (because left sides are the same, but right sides differ). This gives you that option D is false.

4. At last, subtract 4 from the equation :

this equation differs from the equation in option E (because left sides are the same, but right sides differ). This gives you that option E is false.

**Answer: **correct choices are B and C.

ANSWERED AT 29/01/2020 - 05:36 PM

QUESTION POSTED AT 29/01/2020 - 05:36 PM

Multiply the value by 4 for the next value.

1:4 ratio

1:4 ratio

ANSWERED AT 29/01/2020 - 05:34 PM

QUESTION POSTED AT 29/01/2020 - 05:34 PM

**Answer:**

**The volume of the empty space is 20.57 unit³.**

**Step-by-step explanation:**

Given,

The volume of the box = 96 cubic units,

Also, the cylindrical container is packed inside the box.

We know that,

The volume of a cylinder is,

Where r is the radius of cylinder,

h is its height,

Here, r = = 2 unit ( Radius = Diameter / 2 )

And, h = 6 units

Thus, the volume of the cylindrical container is,

Hence,** the volume of the empty space between the cylinder and the box **= Volume of the box - Volume of the container

ANSWERED AT 29/01/2020 - 05:33 PM

QUESTION POSTED AT 29/01/2020 - 05:33 PM

we know that the expression is equal to

Subtract the two fractions

therefore

__the answer is__

**the quantity of over **

ANSWERED AT 29/01/2020 - 05:33 PM

QUESTION POSTED AT 29/01/2020 - 05:33 PM

1,5 I think because the x is negative so it would become positive and the y would stay the same.

ANSWERED AT 29/01/2020 - 05:32 PM

QUESTION POSTED AT 29/01/2020 - 05:32 PM

F(x) = 3x³ - 12x² - 15x

1) Factor Outside: 3x( x² - 4x - 5)

Factor Inside: 3x(x + 1)(x - 5)

2) Set Equal To 0:

3x = 0

x + 1 = 0

x - 5 = 0

3) Solve:

x = 0, -1, 5

1) Factor Outside: 3x( x² - 4x - 5)

Factor Inside: 3x(x + 1)(x - 5)

2) Set Equal To 0:

3x = 0

x + 1 = 0

x - 5 = 0

3) Solve:

x = 0, -1, 5

ANSWERED AT 29/01/2020 - 05:31 PM

QUESTION POSTED AT 29/01/2020 - 05:31 PM

Parenthesis statements are evaluated first such that 7-2 Is 5.

From left to right, multiplication and division are evaluated: 5×4=20 6/3 =2

Finally addition and subtraction equating finally to: 32 + 20 - 2 = 50

From left to right, multiplication and division are evaluated: 5×4=20 6/3 =2

Finally addition and subtraction equating finally to: 32 + 20 - 2 = 50

ANSWERED AT 29/01/2020 - 05:31 PM

QUESTION POSTED AT 29/01/2020 - 05:31 PM

Hello,

√(5-x)=4

==>5-x=16

==>x=-11

Proof:

√(5-(-11))=√16=4

√(5-x)=4

==>5-x=16

==>x=-11

Proof:

√(5-(-11))=√16=4

ANSWERED AT 29/01/2020 - 05:31 PM

QUESTION POSTED AT 29/01/2020 - 05:31 PM

6x/-4 = 6(-1/2)

6x/-4 = - 3...multiply by -4

6x = -3 * -4

6x = 12

x = 2

6x/-4 = - 3...multiply by -4

6x = -3 * -4

6x = 12

x = 2

ANSWERED AT 29/01/2020 - 05:30 PM

QUESTION POSTED AT 29/01/2020 - 05:30 PM

Area x² = 10

x = √10 ≈ 3.16227

**x ≈ 3.162 mile** to the nearest thousandth. Option C.

x = √10 ≈ 3.16227

ANSWERED AT 29/01/2020 - 05:30 PM

QUESTION POSTED AT 29/01/2020 - 05:30 PM

**Answer:**

APEX - y = -1/3x +10

**Step-by-step explanation:**

ANSWERED AT 29/01/2020 - 05:29 PM

QUESTION POSTED AT 29/01/2020 - 05:29 PM

Yes so whats the question

ANSWERED AT 29/01/2020 - 05:29 PM

QUESTION POSTED AT 29/01/2020 - 05:29 PM

G(x) = 3x - 5

let g(x) = y

y = 3x - 5

y + 5 = 3x

3x = y + 5

x = (y + 5)/3

From y = g(x), x = g⁻¹(y)

x = (y + 5)/3

g⁻¹(y) = (y + 5)/3

g⁻¹(x) = (x + 5)/3

let g(x) = y

y = 3x - 5

y + 5 = 3x

3x = y + 5

x = (y + 5)/3

From y = g(x), x = g⁻¹(y)

x = (y + 5)/3

g⁻¹(y) = (y + 5)/3

g⁻¹(x) = (x + 5)/3

ANSWERED AT 29/01/2020 - 05:29 PM

QUESTION POSTED AT 29/01/2020 - 05:29 PM

5,8, and 10 because you're scale factor is by 2, so you multiply your originals by the scale factor

ANSWERED AT 29/01/2020 - 05:29 PM

QUESTION POSTED AT 29/01/2020 - 05:29 PM

**Answer:**

**Step-by-step explanation:**

Given the legs of right angled triangle 4 and 5 units. we have to find the length of hypotenuse.

**By Pythagoras theorem,**

**In right angled triangle **the square of the length of the hypotenuse is equal to sum of squares of the lengths of other two sides

**Hence**,

ANSWERED AT 29/01/2020 - 05:29 PM

QUESTION POSTED AT 29/01/2020 - 05:29 PM

F(x) = 3x + 1

let f(x) = y

y = 3x + 1

y - 1 = 3x

3x = y - 1

x = (y - 1)/3

From y = f(x), x = f⁻¹(y)

x = (y - 1)/3

f⁻¹(y) = (y - 1)/3

f⁻¹(7) = (7 - 1)/3 = 6/3 = 2

f⁻¹(7) = 2

let f(x) = y

y = 3x + 1

y - 1 = 3x

3x = y - 1

x = (y - 1)/3

From y = f(x), x = f⁻¹(y)

x = (y - 1)/3

f⁻¹(y) = (y - 1)/3

f⁻¹(7) = (7 - 1)/3 = 6/3 = 2

f⁻¹(7) = 2

ANSWERED AT 29/01/2020 - 05:28 PM

QUESTION POSTED AT 29/01/2020 - 05:28 PM

Quotient: 2x^3 - 6x^2 +16x - 47 with a remainder of 369/(2x + 8)

ANSWERED AT 29/01/2020 - 05:27 PM

QUESTION POSTED AT 29/01/2020 - 05:27 PM

ANSWERED AT 29/01/2020 - 05:27 PM

QUESTION POSTED AT 29/01/2020 - 05:27 PM